STRATEGI DAKWAH JAM’IYATUL QURRO’ WAL HUFFADZ AL-AMANAH DALAM MENINGKATKAN KARAKTER RELIGIUS MAHASISWA INSTITUT PESANTREN KH. ABDUL CHALIM DI MOJOKERTO - Achmad Qusyairiy Assayuuthiy; Sukataman (IAINU Kebumen, 2026)
This study aims to analyze the da‘wah strategies of Jam’iyyatul Qurro’ wal Huffadz (JQH) Al-Amanah in enhancing the religious character of students at Institut Pesantren KH. Abdul Chalim Mojokerto. This research employs a qualitative approach using field research with a phenomenological perspective. Data were collected through observation, in-depth interviews, and documentation involving administrators, members, and alumni of JQH Al-Amanah. Data validity was ensured through triangulation techniques. The findings indicate that the da‘wah strategies of JQH Al-Amanah are implemented through systematic da‘wah management, including planning, organizing, implementation, and supervision. The da‘wah practices are based on Muhammad Abu al-Fath al-Bayyanuni’s da‘wah strategy theory, which consists of three approaches: sentimental strategy (al-manhaj al-‘athifi), rational strategy (al-manhaj al-‘aqli), and sensory strategy (al-manhaj al-hissi). These strategies are applied through Qur’anic recitation, memorization programs, Islamic studies, moral development, and continuous religious evaluation. The implementation of these da‘wah strategies has proven effective in enhancing students’ religious character, as reflected in the development of Qur’anic values, commitment to worship, mutual assistance, discipline, and emotional-spiritual balance within campus life. Therefore, the da‘wah strategy of JQH Al-Amanah plays a significant role in fostering students’ religious character in an Islamic higher education environment.